Governing the yarshagumba 'gold rush': a comparative study of governance systems in the Kailash Landscape in India and Nepal. Issue 1 (April 2019) - Wallrapp, Corinna; Keck, Markus; Faust, Heiko
Under present conditions of economic globalization, social-ecological systems undergo rapid changes. In this context, internal and external forces put heavy pressure on the governance systems of commons to adapt effectively. While institutional learning has been identified as a key element for the adaptive governance of social-ecological systems, there is still limited knowledge of what roles communities and governmental actors play in these processes. In this study, we take the case of yarshagumba (English: caterpillar fungus), a formerly non-valued product in the Himalayas, which has recently been transformed into a highly valuable resource within a short time. We compare the governance systems in collection sites in the Kailash Landscape in India and Nepalby using an analytical framework developed by Pahl-Wostl. Our findings show that in these remote mountain areas, communities and community-led organizations are highly flexible in responding to immediate resource value changes by establishing communal management arrangements. At the same time, however, communities have difficulties to enforce their newly developed informal and formal arrangements. During the process of learning the link between the amendment of arrangements on community-level and the revision of formal policies and frames at the state or national level is only partly established. Against this background, we argue that in the context of rapid change, adaptive governance requires the concerted interaction of actors at the local and the national levels in order to enable the sustainable use of common pool natural resources.